Enthusiasm to Avoid Stunting (Sehati) - Apriani, Yesintha; Imanullah, Dwi Adzwin; Kurniawan, Salsabila Putri; Prastika, Faradila Fajar; Nasywaa, Fitria Ananta; Sari, Trianita Nurnayla; Herlambang, Faradi Deo; Nalarsih, Paris; Mayithoh, Rifki Zahrani; Pramesthi, Friska Wahyu Idha; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Stunting is a significant public health problem with long-term impacts on child growth and development. This article highlights the importance of enthusiasm and awareness in preventing stunting through an integrated approach that involves increasing maternal knowledge, fulfilling nutritional needs during pregnancy, providing exclusive breastfeeding, providing appropriate complementary foods, and regularly monitoring toddler growth. This approach also emphasizes the importance of a clean environment and access to clean water and adequate sanitation. Through the "Sehati (Spirit to Avoid Stunting)" program, it is hoped that synergy will be created between individuals, families, communities, and the government to significantly reduce stunting rates. Awareness and shared commitment are key to supporting optimal child growth and development for a healthier and more productive future.